2006
DOI: 10.1007/s00049-005-0333-5
|View full text |Cite
|
Sign up to set email alerts
|

Can the ratio of aromatic skeletons explain cross-species responses within evolutionarily conserved Ostariophysan alarm cues?: testing the purine-ratio hypothesis

Abstract: While the response to damage-released chemical alarm cues within the superorder Ostariophysi appears to be highly conserved across species, it is generally observed that the intensity of response to heterospecific alarm cues decreases with increasing phylogenetic distance. Recent studies have demonstrated that purine-N-oxides function as chemical alarm cues within Ostariophyian fishes and that the nitrogen-oxide functional group is conserved as the chief molecular trigger. According to the purine-ratio hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 28 publications
(28 reference statements)
4
29
0
Order By: Relevance
“…Of particular interest is that both cichlids and trout exhibited similar response intensities towards disturbance cues collected from conspecific and heterospecific donors, demonstrating a lack of specificity. This response towards the disturbance cues of phylogentically distant heterospecifics differs considerably from the response pattern seen in the damage-release alarm cues, which are characterized by strong conservation within taxonomic groups (Mirza & Chivers 2001b;Brown et al 2003;Kelly et al 2006). If disturbance cues are indeed a generalized metabolic byproduct, as previously suggested, then prey guild members foraging on a common diet may be expected to produce disturbance cues that are readily recognized by both conspecifics and heterospecifics.…”
Section: Discussionmentioning
confidence: 66%
“…Of particular interest is that both cichlids and trout exhibited similar response intensities towards disturbance cues collected from conspecific and heterospecific donors, demonstrating a lack of specificity. This response towards the disturbance cues of phylogentically distant heterospecifics differs considerably from the response pattern seen in the damage-release alarm cues, which are characterized by strong conservation within taxonomic groups (Mirza & Chivers 2001b;Brown et al 2003;Kelly et al 2006). If disturbance cues are indeed a generalized metabolic byproduct, as previously suggested, then prey guild members foraging on a common diet may be expected to produce disturbance cues that are readily recognized by both conspecifics and heterospecifics.…”
Section: Discussionmentioning
confidence: 66%
“…Previous work suggests that the alarm pheromone system may be comprised of a suite of purine compounds sharing a common NO functional group (Brown et al 2000) and that species-specific ratios of these compounds might account for the observed decline in response intensity (Kelly et al 2006). This suggests that while the NO molecular trigger may be highly conserved in ostariophysans (Brown et al 2000) as an alarm pheromone system (Brown et al 2003), the exact chemical structure of alarm substance in ostariophysans is unknown, and additional work on the isolation of the alarm substance is required.…”
Section: Discussionmentioning
confidence: 98%
“…Pfeiffer (1963) demonstrates that the ostariophysan alarm substance is associated with the presence of specialized epidermal cells called club cells. It has been suggested that the alarm substance is chemically similar in all ostariophysan fish and may induce alarm reaction in sympatric heterospecifics (Schutz 1956;Wisenden et al 1995), although it was observed that the intensity of the response to heterospecific alarm cues decreases with increasing phylogenetic distance (Kelly et al 2006). Pfeiffer et al (1985a) suggest that the active component of the alarm substance is a small heterocyclic compound, likely hypoxanthine-3N-oxid.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Alarm substances of the Osteriophysan superorder of fishes were identified from numerous species in the past (Pfeiffer, 1977;Pfeiffer et al, 1985). A common chemical structure shared across these multiple species was found (Kelly et al, 2006;Brown et al, 2000;2003). Based upon this discovery, a compound mimicking this common chemical element was synthesized.…”
Section: H3no the Synthetic Alarm Substancementioning
confidence: 99%